Association between serum uric acid and colorectal cancer risk in European population: a two-sample Mendelian randomization study - Zhou, Jinsong; Fu, Rong; Zhang, Juwei; Zhang, Suhong; Lin, Zhifeng; Lin, Zheng; Liu, Xin; Xu, Xiaolu; Chen, Yulun; Hu, Zhijian (Frontiers in Oncology, 2024)
Objectives This study aimed to explore the potential causal associations between serum uric acid (SUA) and the risk of colorectal cancer, colon cancer and rectal cancer. Methods Twenty-six SUA-related single nucleotide polymorphisms which were identified by a large meta-analysis of genome-wide association studies (GWASs) were used as instrumental variables in the two-sample Mendelian randomization (MR) study. Meta-analyses were used to synthesize the results of multiple GWASs which were extracted from the MRC Integrative Epidemiology Unit GWAS database for each type of cancer. The inverse variance weighted (IVW) method was used as the primary MR method to analyze the association between SUA and colorectal cancer risk. Several sensitivity analyses were performed to test the robustness of results. Results The IVW method showed that there were no causal relationships between SUA and the risk of colorectal cancer [odds ratio (OR): 1.0015; 95% confidence interval (CI): 0.9975–1.0056] and colon cancer (OR: 1.0015; 95% CI: 0.9974–1.0055). The SUA levels were negative correlated with rectal cancer risk (OR: 0.9984; 95% CI: 0.9971–0.9998). The similar results were observed in both males (OR: 0.9987; 95% CI: 0.9975–0.9998) and females (OR: 0.9985; 95% CI: 0.9971–0.9999). The sensitivity analyses suggested no evidence of heterogeneity or horizontal pleiotropy. The leave-one-out analyses showed that one SNP (rs1471633) significantly drove the causal effect of SUA on rectal cancer risk. The MR-Egger regression and weighted median both showed that there were no causal relationships between SUA and the risk of colorectal cancer and its subtypes. Conclusion Overall, there was no linear causal association between SUA and the risk of colorectal cancer. However, further research is needed to investigate the role of higher SUA levels such as hyperuricemia or gout in the occurrence of colorectal cancer.